Dari "Bisa" Menjadi "Terbiasa": Analisis Pengembangan Nilai Moral Agama Anak Usia 5–6 Tahun di TK Purnama - Wati, Evi Janria Tri; Ermiana, Ida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of religious and moral values in early childhood aims not only to help children understand positive values but also to apply them consistently in their daily lives. However, a gap is often found between children's ability to perform a behavior and their habit of applying the value independently. This study aimed to analyze the development of religious and moral values among children aged 5–6 years at TK Purnama and to describe the transformation of values from being “able to perform” to becoming “accustomed to performing” based on the Experiential Learning perspective. This study employed a descriptive qualitative approach involving 10 children in Group B aged 5–6 years. Data were collected through observation and interviews and analyzed using the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing. The findings revealed that most children were able to participate in structured religious activities, such as praying and reciting the Qur’an, but had not consistently demonstrated sharing, discipline, politeness, and honesty in everyday situations. These findings indicate a gap between the ability to perform values and the habit of applying them in daily life. From the perspective of Experiential Learning, children had acquired experiences and understanding of the values being taught; however, the consistent application of these values still required reinforcement through habituation, role modeling, and repeated learning experiences. Therefore, the transformation from being “able” to becoming “accustomed” represents a gradual process of value internalization until the values become an integral part of children's character.